Urea-facilitated uptake and nitroreductase-mediated transformation of 2,4,6-trinitrotoluene in soil using vetiver grass - Das, Padmini K.; Sarkar, Dibyendu; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2015)
Limited bioavailability of hydrophobic nitroaromatic compounds such as 2,4,6-trinitrotoluene (TNT) is a major challenge toward developing an effective in situ bioremediation method for active or former military sites. A greenhouse-scale study evaluated the efficiency of a stimulative phytoremediation method using urea, a common nitrogen fertilizer, as a solubilizing agent to facilitate TNT uptake by vetiver grass (Chrysopogon zizanioides L.). Kinetics of TNT removal by vetiver from the TNT-spiked soil (100 mg kg−1) was fast (up to 0.004 kg d−1 g−1), following a pseudo first-order reaction rate. Vetiver showed high affinity for TNT (>80% removal within 22 days), and significant root-to-shoot TNT translocation (average 37%). Soil TNT removal rates by vetiver were significantly (p < 0.0001) enhanced by urea. Urea application at agronomically-recommended nitrogen rates (125–350 mg kg−1 soil) was optimum for TNT uptake by vetiver grass. Monoaminodinitrotoluenes and 1,3,5-trinitrobenzene were the main TNT metabolites detected in plant tissues, posing little, if any, influence on plant health. Enhanced activity of nitroreductase enzyme (NR) in TNT treated vetiver plants was observed, which coincides with the prevalence of amino-based TNT metabolites within plant tissues, indicating an effective biochemical defense mechanism against TNT toxicity.
Keywords: Vetiver; TNT; Phytoremediation; Urea; Nitroreductase